STRATEGI SEGMENTASI PASAR UNTUK PENINGKATAN JUMLAH NASABAH DI BMT SIDOGIRI CAPEM SEMPU - Alifudin, Mochamad Zain; Zamroji, Yunus (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purposes of this study are: 1) To determine the existing market segmentation in BMT Sidogiri Capem Sempu, 2) To determine the determination of the segmentation, 3) Determine the impact of market segmentation in increasing the number of customers at BMT Sidogiri Capem Sempu. The results of this study are the existing segmentation in BMT, namely geographic, demographic and psychographic segmentation which in practice market segmentation is used as a tool to determine the target market to be targeted and determine the target market. So that in marketing existing products will achieve maximum results and in accordance with company targets. As for the considerations before choosing a market determination strategy, several considerations need to be made, namely by determining the area and value of various market segments, so that segmentation allows BMT to be more focused in allocating funds. Segmentation accompanied by the selection of a target market will provide a reference and basis for determining positioning. Segmentation is a key factor to beat competitors. Because consumers are too heterogeneous, BMT needs to group the market into market segments.